Efektivitas Fungsi Komisi Pemilihan Umum Kabupaten Bengkulu Utara dalam Sosialisasi Pemilihan Bupati dan Wakil Tahun 2020 - Hevi Dwi Jayanti; Aidinil Zetra; Asrinaldi Asrinaldi (Mahesa Research Center, 2023)
This article aims to describe the process of implementing door to door socialization carried out by the General Election Commission of North Bengkulu Regency for voters in the midst of Covid-19 conditions and to determine the effectiveness of door to door socialization carried out by the General Election Commission of Bengkulu Regency as a form of effectiveness of the institution's function in socialization in pandemic period. The problem focuses on the effectiveness of the KPU's function in socializing the election of Regent and Deputy in North Bengkulu Regency. In order to approach this problem, Christopher C Hood's reference theory is used. Data was collected through interviews and documentation methods and analyzed qualitatively. This study concludes that during the implementation of socialization carried out by the North Bengkulu Regency KPU through four categories of tools that influence the effectiveness of institutional functions, they were only effective in participation tools, while the other three tools such as regulations, incentives and law enforcement showed ineffective results. The implementation of door to door outreach, which was used as a new media, apparently did not produce effective results. This can also be seen from resource capacity factors related to system culture and accountability factors related to implementing reports which also show ineffective results. However, the North Bengkulu Regency KPU has tried its best to carry out socialization regarding the 2020 Regent and Deputy Regent elections.